Cooperative Learning Implementation Model to Improve Mathematics Learning Outcomes - Manurung, Alberth Supriyanto; Halim, Abdul; Rosyid, Ainur (Jurnal Basicedu, 2022)
The purpose of this study was to determine the Implementation Model of Cooperative Learning to improve Mathematics Learning Outcomes. The research method used was a survey method and used regression analysis techniques and simple correlation. This research was conducted at SDN Kenari 07 Pagi, Salemba sub-district with n = 36 using the Cluster Sampling technique. (1) The application of Cooperative Learning has an influence on mathematics learning outcomes; (2) Interest has an influence on the Implementation of Cooperative Learning; (3) The background of students has an influence on the application of cooperative learning; (4) Intelligence has an influence on the Application of Cooperative Learning. Based on this research, it is expected that the mathematics learning outcomes of fifth grade elementary school students can be improved by the influence of the application of cooperative learning, because the verification results prove that the application of cooperative learning is a significant determining factor. In many ways the characteristic enhancement model is used to solve educational problems and one of them is the Cooperative Learning Model which certainly affects the development of children where each child has different characteristics from one another so that it can show the child's character in solving the problems faced.Â